India then & now - Sanghvi, Vir.; Mukherjee, Rudrangshu; Kapoor, Pramod (New Delhi : Lustre Press/Roli Books, 2005)
Pictorial representation of India.
India now -- India then.
Texts and photographs of each section in opposite direction and pagination.
Keywords: India -- Pictorial works